Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Weeping Waters: The Treaty of Waitangi and Constitutional Change - Mulholland, Malcolm; Tawhai, Veronica (Huia Publishers, 2010)
Weeping Waters is a must read for anyone who wants to be informed about the current debate regarding the Treaty of Waitangi and a constitution for Aotearoa New Zealand. The book features essays from eighteen well-known and respected Maori figures including Professor Margaret Mutu, Bishop Muru Walters, Judge Caren Fox and lawyer Moana Jackson. This is the first book in recent years to offer a M?ori opinion on the subject of constitutional change. It shows how M?ori views have been ignored by successive governments and the courts and how M?ori have attempted to address constitutional issues in the past. The book also provides suggestions for a pathway forward if the Treaty of Waitangi is to be fully acknowledged as the foundation for a constitution for Aotearoa New Zealand.
Keywords: constitution; history; māori views

Constitutional Transformation - Mulholland, Malcolm; Tawhai, Veronica (Weeping Waters: The Treaty of Waitangi and Constitutional Change, 2017)
"Weeping Waters is a must read for anyone who wants to be informed about the current debate regarding the Treaty of Waitangi and a constitution for Aotearoa New Zealand. The book features essays from eighteen well-known and respected Maori figures including Professor Margaret Mutu, Bishop Muru Walters, Judge Caren Fox and lawyer Moana Jackson. This is the first book in recent years to offer a Maori opinion on the subject of constitutional change. It shows how Maori views have been ignored by successive governments and the courts and how Maori have attempted to address constitutional issues in the past. The book also provides suggestions for a pathway forward if the Treaty of Waitangi is to be fully acknowledged as the foundation for a constitution for Aotearoa New Zealand."–Publisher.
Keywords: constitution; crown law; tiriti o waitangi/treaty of waitangi

Youth Engagement - Tawhai, Veronica (New Zealand government and politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Always Speaking: The Treaty of Waitangi and Public Policy - Tawhai, Veronica; Gray-Sharp, Katarina (Huia Publishers, 2011)
This is a collection of papers that examine the current place of the Treaty of Waitangi in core public policy areas. The authors analyse the tensions and dynamics in the relationship between Maori and the Crown in their areas of expertise, detail the key challenges being faced, and provide insights on how these can be overcome. The policy areas covered in the collection span the environment, Maori and social development, health, broadcasting, the Maori language, prison and the courts, local government, research, science and technology, culture and heritage, foreign affairs, women's issues, labour, youth, education, economics, housing and the electoral system.
Keywords: civil Rights